Tinjauan Perizinan Wisata Air Terjun Tancak Panti (Kajian atas PP RI Nomor 3 Tahun 2008 Tentang Perubahan atas PP Nomor 6 Tahun 2007 Tentang Tata Hutan Dan Penyusunan Rencana Pengelolaan Hutan, Serta Pemanfaatan Hutan) - Susanti, Dinda Rizki; Musfianawati, Musfianawati; Hoiru Nail, Muhammad; Laily Mufid, Firda (WELFARE STATE Jurnal Hukum, 2023)
At the present time, traveling has become secondary requirement for people, to get rid of fatigue after work or just entertain themselves. It takes no less amount of people who like nature tourism and ecotourism. In Jember city, there is one very interesting nature tourism called the Tancak Panti Waterfall which is located in Suci Village. However, the question arises : Can the Tancak Panti Waterfall obtain authorization or licence as nature tourism? Does the Suci Village Government and the local community should be apply for requirements and qualifications to granted the licence? The aim in this article is to determine the method of normative and empirical legal research with the typical characteristics of the methods of researching Law. The result of the first discussion is that the Tancak Panti Waterfall Tourism Destination has the right to obtain licence as nature tourism in accordance with Article 33 Number (1) of Government Regulation Number 3 of 2008 on amendments to Government Regulation Number 6 of 2007 concerning Forest Management and Preparation of Forest Management Plans, As well as Forest Utilization which states that the Tancak Waterfall can obtain licence for nature tourism. The result of the second discussion is that the Suci Village Administration and the local community have the right to apply for licence in accordance with Article 67 Paragraph (2) of Government Regulation Number 3 of 2008 regarding amendments to Government Regulation Number 6 of  2007 concerning Forest Management and Preparation of Forest Management Plans, as well as Forest Utilization.